Graduate Student Learning Abroad: Emerging Trend? - Dirkx, John M; Millar, Kristin Janka; Berquist, Brett; Vizvary, Gina (International Higher Education, 2014)
Within the United States and around the world, universities are increasingly sending their graduate students abroad. But we know relatively little about the learning derived from these international experiences or how they contribute to graduate-level education. Researchers at Michigan State University have begun to explore this “black box” of internationalization, providing some answers and raising more questions.